New evidence on the nephrotoxicity of fine particulate matter: Potential toxic components from different emission sources - Fu-Jen Cheng; Chien-Er Huang; Pei-Shih Chen; Yu-Lun Tseng; Chung-Shin Yuan; Ching-Shu Lai (Ecotoxicology and Environmental Safety, 2025)
Associations exist between fine particulate matter (PM2.5) exposure and impaired kidney function. However, the specific mechanisms and components causing renal damage remain unclear. PM2.5 was collected from an industrial and a rural area. Mice were categorized according to exposure, and biochemical, western blotting, histological, and immunohistochemical analyses were performed to evaluate the impact of PM2.5 constituents on their kidneys. To assess the impact of different PM2.5 components on inflammatory responses, a study was conducted by exposing the murine macrophage cell line (RAW 264.7). The study used a chelating resin to remove the influence of heavy metals from the water extract and employed a Toll-like receptor 4 (TLR4) antagonist to eliminate the effects of endotoxin, thereby evaluating the cellular inflammatory responses induced by various PM2.5 components. The major metallic elements at the industrial site were Fe, Mg, Zn, and Ca, whereas those at site Rural were Ca, K, and Mg. PM2.5 water extracts from both sites induced inflammatory cytokine upregulation in the lungs and kidneys, and inflammatory cell infiltration, antioxidant activity downregulation, and elevated levels of kidney injury molecule 1 in the kidneys. Exposure to PM2.5 water extract increased the mRNA levels of tumor necrosis factor-α, interleukin-6, and nitrite production in RAW264.7 macrophages. The inflammatory response and nitrite production induced by the industrial-site PM2.5 water extract were significantly suppressed after treatment with a chelating resin, whereas those from the rural area were suppressed by the Toll-like receptor 4 (TLR4) antagonist. These results suggest that heavy metals are crucial factors in PM2.5-induced cellular inflammatory responses in industrial areas, whereas endotoxin receptor--TLR4 mediated inflammatory pathways are the primary factor responsible for this response in rural areas. Furthermore, at equivalent dosages, the renal toxicity induced by the water-soluble components of rural-site PM2.5 may exceed that from industrial areas.